Safety and effectiveness of bronchial thermoplasty after 10 years in patients with persistent asthma (BT10+): a follow-up of three randomised controlled trials. Issue 5 (May 2021) - Chaudhuri, Rekha; Rubin, Adalberto; Sumino, Kaharu; Lapa e Silva, Jose Roberto; Niven, Robert; Siddiqui, Salman; Klooster, Karin; McEvoy, Charlene; Shah, Pallav L; Simoff, Michael; Khatri, Sumita; Barbers, Richard; et al.
Summary: Background: Bronchial thermoplasty is an endoscopic treatment for uncontrolled asthma. Previous randomised clinical trials have shown that bronchial thermoplasty reduces severe exacerbations in people with asthma. However, the long-term efficacy and safety of bronchial thermoplasty beyond 5 years is unknown. The BT10+ study aimed to investigate the efficacy and safety of bronchial thermoplasty after 10 or more years of follow-up. Methods: BT10+ was an international, multicentre, follow-up study of participants who were previously enrolled in the AIR, RISA, and AIR2 trials and who had 10 or more years of follow-up since bronchial thermoplasty treatment. Data on patient demographics, quality of life, lung function, CT scans (AIR2 participants only), severe exacerbations, and health-care use during the previous year were collected at the BT10+ 10-year outcomes study visit. The primary effectiveness endpoint was durability of the thermoplasty treatment effect, determined by comparing the proportion of participants who had severe exacerbations during the first and fifth years after bronchial thermoplasty treatment with the proportion of participants who had severe exacerbations during the 12-month period before the BT10+ visit. The primary safety endpoint was the absence of clinically significant post-treatment respiratory image changes after bronchial thermoplasty, defined as bronchiectasis or bronchial stenosis as confirmed by pulmonary volumetric high-resolution CT scan at the BT10+ visit (AIR2 participants only). All analyses were done on an intention-to-treat basis. The trial is registered with ClinicalTrials.gov, NCT03243292 . The last patient was enrolled on Dec 11, 2018. The last patient completed follow-up on Jan 10, 2019. Findings: The BT10+ study enrolled 192 (45%) of the 429 participants who were enrolled in the AIR, RISA, and AIR2 trials. The BT10+ participants comprised 136 who received bronchial thermoplasty (52% of the 260 participants who received bronchial thermoplasty in the original trials), and 56 sham or control participants (33% of 169 from the original trials). 18 (32%) sham or control participants received bronchial thermoplasty after the previous trials concluded. The participants included in BT10+ were followed for 10·8–15·6 years (median 12·1 years) post-treatment. Baseline characteristics were similar between participants enrolled in BT10+ and those not enrolled. Participants treated with bronchial thermoplasty had similar proportions of severe exacerbations at the BT10+ visit (34 [25%] of 136 participants) compared with 1 year (33 [24%] of 135 participants; difference 0·6%, 95% CI −9·7 to 10·8) and 5 years (28 [22%] of 130 participants; difference 3·5%, −6·7% to 13·6) after treatment. Quality of life measurements and spirometry were similar between year 1, year 5, and the BT10+ visit. At the BT10+ study visit, pulmonary high-resolution CT scans from AIR2 participants treated with bronchial thermoplasty showed that 13 (13%) of 97 participants had bronchiectasis. When compared with baseline high-resolution CT scans, six (7%) of 89 participants treated with bronchial thermoplasty who did not have bronchiectasis at baseline had developed bronchiectasis after treatment (5 classified as mild, 1 classified as moderate). Participants treated with bronchial thermoplasty after the original study and participants in the sham or control group also had reductions in severe exacerbations at the BT10+ visit compared with baseline. Interpretation: Our findings suggest that efficacy of bronchial thermoplasty is sustained for 10 years or more, with an acceptable safety profile. Therefore, bronchial thermoplasty is a long-acting therapeutic option for patients with asthma that remains uncontrolled despite optimised medical treatment. Funding: Boston Scientific.